Acquisition and maintenance of excellence: the challenges faced by Dutch top-level gymnasts throughout different stages of athletic development - Blijlevens, S. J. E.; Wylleman, P.; Bool, K.; Elferink-Gemser, M. T.; Visscher, C. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The purpose of the present study is to identify the within-career challenges top-level gymnasts experience during the initiation, development and mastery stage of athletic development in training sessions, competition, and in daily life. In-depth interviews are used to explore the perceived challenges of 16 talented and elite gymnasts (M = 16.5 years, SD = 4.6 years). Participants are divided into three groups, according to the stage of their athletic development. Several challenges are perceived in all stages of athletic development (e.g. learning new elements, dealing with stress under pressure, dealing with distractions and managing their dual career). As the number of different challenges increases as the gymnasts reach the mastery stage, challenges seem to become more personal and specific than in previous stages. The study shows obvious differences in the nature of the perceived challenges for different stages of athletic development, which provides useful insights for those who work with talented and elite athletes.